2008
DOI: 10.1111/j.1365-2621.2008.01731.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flavonoids on the oxidative stability of corn oil during deep frying

Abstract: To study the effect of flavonoids on the stability of frying oil, refined corn oil was analysed periodically for its peroxide value (PV), p-anisidine value (p-AV) and iodine value (IV) after its use for deep-frying of French fries at 180°C for varying periods of time, namely 30, 60 and 90 min. PV and p-AV values increased with respect to time while a decrease in IV was observed with increase in time (P < 0.001). Deep-frying of French fries in corn oil was then carried out in the presence of flavonoids, viz. pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…An increase in the pAVof all the oil samples with frying numbers was observed. These findings are in good agreement with several studies (Naz et al 2008;Chen et al 2014). The statistical analysis results also showed the significant effect (p<0.05) of frying numbers on the increase in pAV of the oils.…”
Section: Change In Peroxide Value (Pv) Of Corn Oil During Fryingsupporting
confidence: 81%
“…An increase in the pAVof all the oil samples with frying numbers was observed. These findings are in good agreement with several studies (Naz et al 2008;Chen et al 2014). The statistical analysis results also showed the significant effect (p<0.05) of frying numbers on the increase in pAV of the oils.…”
Section: Change In Peroxide Value (Pv) Of Corn Oil During Fryingsupporting
confidence: 81%
“…It was stated that the inhibitive effect of phenolic acid was expected to be related to their polarity (Roussis and others 2008). Naz and others (2008) reported that the flavonoids reduced the formation of oxidation in corn oil during deep frying and concluded that the order of antioxidative activity was gallic acid > quercetin > myricetin > cyanidin > pelargonidin. The literature information indicated that gallic acid is a stable and effective antioxidant phenolic acid as stated in our study.…”
Section: Resultsmentioning
confidence: 99%
“…In general, these compounds have redox properties and act as free radical scavengers (Lai and others 1991; Shahidi and others 1992). Food researchers are also interested in natural phenolics because of their potent quality retarding the oxidation effects as antioxidants in edible oils (Xiaoying and Ahn 1998; Naz and others 2004, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Although the structure‐antioxidant activity relationship of flavonoids has been well defined in hydrophilic systems , studies dealing with this in hydrophobic systems are scarce. Free flavonoids, mainly quercetin, myricetin, morin, (+)catechin, (−)epigallocatechin, (−)epicatechin, and kaempferol, have been incorporated in different lipid systems with varying degrees of success in terms of oxidative stability, such as methyl linoleate , canola oil , cottonseed oil , corn oil , or fish oil . The antioxidant activity found in methyl linoleate and purified sunflower oil was related to the number of phenolic hydroxyl groups, 2,3 double bond in the C‐ring and a glycoside moiety in the molecule .…”
Section: Introductionmentioning
confidence: 99%